Sosialisasi Dan Penyiapan Label Halal Bagi Pelaku Industri Rumah Tangga Di Kecamatan Pulau Hiri Kota Ternate - Sirat, Abdul Hadi; Jannang, Abdul Rahman (Patria Artha Journal of Community (PKM), 2021)
The household industry is an economic development through the transformation of resources using simple tools. The household industry is involved in the change from labor-intensive to capital intensive methods. The household industry is usually built in an area close to the raw materials that are the raw materials of the industry. The existence of household industry in the village has an important meaning in the framework of national development. Because of the existence of the household industry is a solution for the undeveloped workforce and economic improvement of the village community. However, the strategic position of the household industry in various places has not been supported by facilities and infrastructure that can improve the effectiveness and efficiency of rural economic life. The existence of cracker household industry in Hiri Island Subdistrict greatly affects the social life of local people.  With the household industry of food products that can produce hundreds of thousands to millions of rupiah every month.  So this indicates how important the activities of IRT activities have an important meaning in the framework of national development. Because the existence of the household industry is a solution for the undeveloped workforce and economic improvement of the village community, so that welfare and a decent life enjoyed This community service activity will socialize and fulfill the understanding of the community on the importance of halal principles and provisions in the JPH Law.. The community, especially IRT actors, can understand that the application of halal standards can have an impact on increasing the market capacity for their products. The understanding of the community that facilitates the importance of the implementation of halal standards will facilitate the way for the establishment of halal zones, which in particular in this program will be pursued in the District of Hiri Island. This socialization recommendation will also be submitted to the government of Ternate City, so that Hiri Island may be used as a place for halal-lying products, such as smoked fish products and banana rips.